International Capital Flow Pressures - Goldberg, Linda (IMF Working Papers; Working Paper, 2018)
This paper presents a new measure of capital flow pressures in the form of a recast Exchange Market Pressure index. The measure captures pressures that materialize in actual international capital flows as well as pressures that result in exchange rate adjustments. The formulation is theory-based, relying on balance of payments equilibrium conditions and international asset portfolio considerations. Based on the modified exchange market pressure index, the paper also proposes the Global Risk Response Index, which reflects the country-specific sensitivity of capital flow pressures to measures of global risk aversion. For a large sample of countries over time, we demonstrate time variation in the effects of global risk on exchange market pressures, the evolving importance of the global factor across types of countries, and the changing risk-on or risk-off status of currencies.